Protected areas as a basis for biodiversity conservation and ecosystem services in Europe: assessment of Ukraine’s contribution - Chumachenko, O.; Kryvoviaz, Ye.; Kustovska, O.; Kolhanova, I. (Land Management, Cadastre and Land Monitoring, 2022)
The article analyzes the structure of nature conservation areas in a number of European countries. The necessity of conducting a study of the state and features of the formation of natural territorial complexes has been determined. In connection with this, a significant volume of bibliographic and electronic Internet sources, both foreign and domestic authors and researchers, has been worked out. The information basis of the research is statistical data of the State Geocadastre of Ukraine, Eurostat, and the European Environment Agency, which made it possible to analyze the state of nature conservation areas. The role of nature conservation areas as the basis for the preservation of biodiversity and ecosystems and their functions of the territory is substantiated and determined. The author’s assessment of the state of nature conservation areas is provided and an approach to calculating the conservation index of European countries is proposed. An analysis of the structure of nature conservation areas in Europe and determination of directions for the expansion of the areas of the latter was carried out. It was determined that in most developed countries, the basis of such territories are: forests, natural pastures, shrubs, water and wetlands, land without vegetation cover. That is, the prospective inclusion or granting of the status of nature conservation areas and eco-networks is a significant potential for nature conservation and improvement of biodiversity conservation and provision of ecosystem services.Key words: nature reserve fund, land use, nature use, territory, ecological network, biological diversity.